Whole genome analysis of two sympatric human Mansonella: Mansonella perstans and Mansonella sp “DEUX” - Rodi, Miriam; Gross, Caspar; Sandri, Thaisa Lucas; Berner, Lilith; Marcet-Houben, Marina; Kocak, Ersoy; Pogoda, Michaela; Casadei, Nicolas; Köhler, Carsten; Kreidenweiss, Andrea; Agnandji, Selidji Todagbe; Gabaldón, Toni; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Mansonella species are filarial parasites that infect humans worldwide. Although these infections are common, knowledge of the pathology and diversity of the causative species is limited. Furthermore, the lack of sequencing data for Mansonella species, shows that their research is neglected. Apart from Mansonella perstans, a potential new species called Mansonella sp “DEUX” has been identified in Gabon, which is prevalent at high frequencies. To further determine if Mansonella sp “DEUX” is a genotype of M. perstans, or if these are two sympatric species, we successfully generated whole genomes for M. perstans as well as for Mansonella sp “DEUX”. Phylogenetic analysis based on annotated protein sequences as well as the mitogenomes, support the hypothesis of two distinct species. The inferred evolutionary analysis suggests, that M. perstans and Mansonella sp “DEUX” have separated around 778,000 years ago. The availability of whole genome data will allow further investigations of these species.